Trip to Jerusalem brings Christianity alive for Armenian youth - Natcharian, Lisa (Տպարան Սրբոյ Յակոբեանց)
Unprecedented access, Touching services, Eye-opening visits, Heart-warming fellowship, Strengthened Christian ties.
Keywords: Christianity; Armenian church